PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA PENGGUNA TRANSPORTASI UMUM BUS TRANS BATAM) - Basowa, Ardida Ponty; Setiawan, Joko (SCIENTIA JOURNAL, 2019)
Trans Batam is a mode of public transportation offered by the Batam city government to the public. In an effort to maintain relationships with customers, the quality of services and facilities is key in maintaining customer and providing high value through customer satisfaction. The purpose of this study was to determine the effect of service quality and facilities on consumer satisfaction on users of Trans Batam bus transportation. The method used is a quantitative method with a type of causality research. The population in this study were trans Batam bus passengers. While the study sample consisted of 100 respondents who used purposive sampling technique. Based on this research, the hypothesis testing between service quality and facility variables partially and simultaneously has a significant effect on consumer satisfaction, case studies on Transs Batam bus public transportation users. These results indicate that the better the quality of services and facilities provided will increase customer satisfaction as users of public transportation services.